The medical cost of abusive head trauma in the United States - Peterson, C.; Xu, L.; Florence, C.; Parks, S.; Miller, Ted; Barr, R.; Barr, M.; Steinbeigle, R. (American Academy of Pediatrics, 2014)
OBJECTIVES: Health consequences of shaken baby syndrome, or pediatric abusive head trauma (AHT), can be severe and long-lasting. We aimed to estimate the multiyear medical cost attributable to AHT. METHODS: Using Truven Health MarketScan data, 2003–2011, we identified children 0 to 4 years old with commercial or Medicaid insurance and AHT diagnoses. We used exact case–control matching based on demographic and insurance characteristics such as age and health plan type to compare medical care between patients with and without AHT diagnoses. Using regression models, we assessed service use (ie, average annual number of inpatient visits per patient) and inpatient, outpatient (including emergency department), drug, and total medical costs attributable to an AHT diagnosis during the 4-year period after AHT diagnosis. RESULTS: We assessed 1209 patients with AHT and 5895 matched controls. Approximately 48% of patients with AHT received inpatient care within 2 days of initial diagnosis, and 25% were treated in emergency departments. AHT diagnosis was associated with significantly greater medical service use and higher inpatient, outpatient, drug, and total costs for multiple years after the diagnosis. The estimated total medical cost attributable to AHT in the 4 years after diagnosis was $47 952 (95% confidence interval [CI], $40 219–$55 685) per patient with AHT (2012 US dollars) and differed for commercially insured ($38 231 [95% CI, $29 898–$46 564]) and Medicaid ($56 691 [95% CI, $4290–$69 092]) patients. CONCLUSIONS: Children continue to have substantial excess medical costs for years after AHT. These estimates exclude related nonmedical costs such as special education and disability that also are attributable to AHT.